Pelatihan Penerapan AI untuk Analisis Beban Kerja di PT ASD - Atep Atep Afia Hidayat; Yudi Gunardi; Hadi Pranoto; Muhammad Kholil; Jakfat Haekal (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2025)
Employee productivity is a key determinant of organizational competitiveness; however, manual workload analysis often leads to imbalances between employees’ capacity and assigned tasks, resulting in inefficiency and reduced well-being. This program aims to provide training on the application of Artificial Intelligence (AI), particularly Artificial Neural Networks, for workload analysis to optimize task distribution and enhance productivity at PT Anugerah Sarana Dinamika. The training consisted of a needs assessment, theoretical sessions on AI, hands-on practice in developing a prototype based on company workload data, mentoring, and workload scenario simulations. Evaluation using pre–post tests on a Likert scale showed a significant improvement in participants’ understanding of AI concepts (average score increased from 2.1 to 4.2), with 80% of participants able to operate the workload analysis prototype and an overall satisfaction rate of 88%. The program successfully improved participants’ digital literacy and technical skills and demonstrated the effectiveness of AI in supporting sustainable human resource management transformation.